Novel hyphomycetous fungi associated with bamboo from Sichuan, China - Yu, Xian-Dong; Zhang, Sheng-Nan; Liu, Jian-Kui (Phytotaxa, 2024)
During an ongoing investigation of bambusicolous fungi in Sichuan province, China, five hyphomycetous taxa were collected and recognized as members of Sordariomycetes. Based on morphological comparisons, culture characteristics, and the multi-locus phylogenetic analyses of combined SSU, ITS, LSU, rpb2 and tef1α sequence dataset, five species, viz. Conioscypha sichuanensis, Conlarium guizhouense, Rhexoacrodictys fimicola, R. melanospora, Wongia bambusae are identified. Conioscypha sichuanensis formed a sister lineage to Conio. bambusicola, which was also found from a bamboo host but can be distinguished from Conio. sichuanensis by different conidial shape. Wongia bambusae is characterized by unbranched, septate conidiophores and cylindric-fusiform conidia, and is most similar to W. ficherai. However, they are phylogenetically distinct. Conlarium guizhouense and R. melanospora, were recollected from the bamboo hosts in terrestrial habitats and reported as new host records in this study. Detailed descriptions and notes on the phylogenetic placement of these species are provided.